Biomaterials: Monolayer Graphene Coating of Intracortical Probes for Long‐Lasting Neural Activity Monitoring (Adv. Healthcare Mater. 18/2019). Issue 18 (19th September 2019) - Bourrier, Antoine; Shkorbatova, Polina; Bonizzato, Marco; Rey, Elodie; Barraud, Quentin; Courtine, Gregoire; Othmen, Riadh; Reita, Valerie; Bouchiat, Vincent; Delacour, Cécile
Abstract : In article number1801331 by Cécile Delacour and co‐workers, an innovative coating method is reported to wrap intracortical probes with continuous graphene monolayers, in order to investigate its impact on the bioacceptance of the implants. Experimental evidence shows that the graphene coating significantly lowers the immune response and enhances the performance and the durability of the probes, paving the way for long‐term reliable recordings of individual motor neurons.